How elastic is East Asian demand for consumption goods? - Willem Thorbecke (Asian Development Bank Institute (ADBI), 2010)
This paper investigates import demand in East Asia. Estimating exchange rate elasticities for countries in the region is difficult because many imports are used to produce goods for re-export. An exchange rate appreciation that reduces East Asian exports will also reduce the demand for imported inputs that are used to produce exports. To correct for this bias this paper examines the imports of consumption goods, since these are intended primarily for the domestic market. Results from several specifications indicate that currency appreciations and increases in income in East Asian countries would significantly increase consumption imports.
Keywords: F32; F41; 330; Konsumgut; Importnachfrage; Außenhandelselastizität; Aufwertung; Außenhandelseffekt; Ostasien